Analisis perubahan sistem perkawinan masyarakat di desa rantau embacang kecamatan tanah sepenggal lintas kabupaten bungo : Adat,kebudayaan,sistem perkawinan,tradisi perkawinan - Faula, Faula; Irwansyahwir, Irwansyahwir (Citizenship Education, Faculty of Education, Jambi University, 2024)
This study aims to describe how the community marriage procession, efforts contained in the community marriage procession and various factors that cause changes in the marriage procession in the marriage customs in Rantau Embacang Village, Tanah Sepenggal Lintas District, Bungo Regency. The results of this study show that there are changes in the community marriage procession from the sirih tanyo-pinang tanyo process, nikah nikah (marriage contract) and collecting tuo, returning lek pado negeri and berelek, where the series in the community marriage system procession are maso kenal, sisik siang,kembang tando establishing the lumbago custom, delivering the lumbago custom handover, nikah, collecting tuo returning lek pado negeri, berelek berkenduri, and collecting tuo closing lek. There is a problem of changes in the marriage procession carried out by the community where this raises the enthusiasm of the community to learn the culture in this marriage system to be minimal, the lack of facilities and infrastructure in carrying out customary marriages and the absence of studios or places to practice the customs. In addition, the lack of trainers who understand the community's marriage procession makes this culture increasingly unpopular.